The role of unions in solving industrial relations problems at Pt. Pos Indonesia (Persero) Bandung Head Office - Rachmawati, Rr.; Lamury, Rafical N.A.; Azis, Yunia Mulyani (Technium Social Sciences Journal, 2021)
In this study the researcher wanted to know how important the roles carried out by trade unions for employees, as well as the problems related to industrial relations, where the problems of industrial relations became a hot issue discussed in the corporate environment. In this research, the role of trade unions and problems in industrial relations were examined. The object of this research is employees at PT. Pos Indonesia (Persero), the center of Bandung, has 80 people using census techniques. This study uses a questionnaire as a data collection tool. The test used to test the research instrument in the form of validity and reliability testing. Data analysis using simple linear regression analysis, correlation coefficient. The results show that the role of trade unions in solving industrial relations problems is in the sufficient category. The results of the calculation of the correlation, the variable union (X) against the variable industrial relations (Y) of 0.773 means that both variables have a positive and significant relationship. The coefficient of determination is 59.7% while the remaining 40.3% is influenced by other variables not examined in this study. Thus, the role carried out by trade unions is very important, but in carrying out its functions, trade unions have not been optimal in their duties to defend employee rights.